Improvement in clinical outcomes and replacement factor VIII use in patients with haemophilia A after factor VIII pharmacokinetic‐guided prophylaxis based on Bayesian models with myPKFiT®. Issue 5 (20th July 2018) - Mingot‐Castellano, M. E.; Parra, R.; Núñez, R.; Martorell, M.
Abstract : Objectives: Patients with severe haemophilia A (HA) receive factor VIII (FVIII) replacement therapy as prophylaxis. myPKFiT ® is an online medical application that allows authorized users to simulate dosing regimens with patient pharmacokinetic (PK) profiles based on only 2 blood samples. Our aim was to assess the impact of using this medical device in routine practice in terms of FVIII consumption and clinical outcomes. Methods: Thirty‐six patients with severe HA on prophylaxis with Advate ® were recruited in 3 centres in Spain. Annual bleeding rate (ABR), annual joint bleeding rate (AJBR) and annual FVIII consumption before and after adjustment were obtained using the patient's clinical history (12 months before) and prospectively recorded data (12 months after), respectively. Adjustment was based on PK parameters provided by myPKFiT ®, joint status and relative risk associated with physical activity and bleeding phenotype. Results: ABR and AJBR were significantly reduced after adjustment in the overall sample (−2.2 ± 1.3, P = .018 and −1.9 ± 1.2, P = .012, respectively) and in patients aged >15 years (−2.6 ± 1.4, P = .011 and −2.0 ± 1.2, P = .005, respectively). Adjustment had an effect on the individual FVIII consumption of most patients: annual amount was reduced in 18 cases and increased in 14. There was no significant effect on the mean amount (198 784 ± 110 387) compared to that used the year prior to myPKFiT ® ‐adjusted prophylaxis (199 466 ± 103 670; P = .737). Discussion: Our results suggest that PK‐guided prophylaxis using myPKFiT ® improved clinical outcomes and optimized FVIII consumption in the study population. This personalized approach may reduce bleeding rates without significantly increasing the overall cost of FVIII therapy.